(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
This report describes and interprets two stratigraphic sections across the regressive part of Baronia Synthem, located near the villages of Flumeri and Vallesaccarda (Ariano Irpino area, Southern Italy). Four different depositional environments have been recognized: fluvial, lagoon, foreshore and shoreface. Fluvial deposits, occurring in the Flumeri section, consist of clast-supported conglomerates, horizontal laminated sands and muddy silts with freshwater ostracod assemblages, indicating deposition in braided river low-sinuosity channels. In the Flumeri section lagoonal deposits are generally represented by structureless layers of dark clay including ostracods of brackish coastal lagoon connected with shallow-marine waters. In the Vallesaccarda section lagoonal sediments only occur as muddy clasts. Foreshore deposits are represented by well sorted yellow sands with low-angle cross lamination; a horizontal layer of stratified gravels outcrops in Vallesaccarda section. The shoreface deposits consist of poorly sorted sands with trough cross stratification formed in a bar and trough system, of symmetric ripples layers, and of abundant mollusc shell debris; in the Vallesaccarda section a tempestite interval generated by storm activity has been found. In Flumeri section littoral and lagoonal facies assemblages alternate; in Vallesaccarda section only nearshore sediments crop out. Nearshore deposits denote a wave-dominated coastal marine environments. These data contribute to a better knowledge of the distribution of paralic facies on the Western margin of the Pliocene Irpinia-Daunia Basin.